Density Matrix Method Application to Resonance Raman Scattering - Dehestani, M. (Asian Journal of Chemistry, 2016)
A projection operator method and density matrix formalism to calculate the rate (transition probability per unit time) of the two-photon process in which the damping effect originating from the molecule-heat bath interaction is properly taken into account and applied this method to resonance Raman scattering.